Process simulations of high-purity and renewable clean H2 production by sorption enhanced steam reforming of biogas - Capa, Alma; Yan, Yongliang; Rubiera, Fernando; Pevida, Covadonga; Gil, María Victoria; Clough, Peter T. (American Chemical Society, 2023)
Renewable clean H2 has a very promising potential for the decarbonization of energy systems. Sorption enhanced steam reforming (SESR) is a novel process that combines the steam reforming reaction and the simultaneous CO2 removal by a solid sorbent, such as CaO, which significantly enhances hydrogen generation, enabling high-purity H2 production. The CO2 sorption reaction (carbonation) is exothermic, but the sorbent regeneration by calcination is highly endothermic, which requires extra energy. Biogas is one of the available carbon-neutral renewable H2 production sources. It can be especially relevant for the energy integration of the SESR process since, due to the exothermic sorption reaction, the CO2 contained in the biogas provides extra heat to the system, which can help to balance the energy requirements of the process. This work studies different process configurations for the energy integration of the SESR process of biogas for high-purity renewable H2 production: (1) SESR with sorbent regeneration using a portion of the produced H2 (SESR+REG_H2), (2) SESR with sorbent regeneration using biogas (SESR+REG_BG), and (3) SESR with sorbent regeneration using biogas and adding a pressure swing adsorption (PSA) unit for hydrogen purification (SESR+REG_BG+PSA). When using biogas as fuel (Cases 2 and 3), these configurations were studied using air and oxy-fuel combustion atmospheres in the sorbent regeneration step, resulting in five case studies. A thermodynamic approach for process modeling can provide the optimal process operating conditions and configurations that maximize the energy efficiency of the process, which are the basis for subsequent optimization of the process at the practical level needed to scale up this technology. For this purpose, process simulations were performed using a steady-state plant model developed in Aspen Plus, incorporating a complex heat exchanger network (HEN) to optimize heat integration. A comprehensive parametric study assessed the effects of biogas composition, temperature, pressure, and steam to methane (S/CH4) ratio on the process performance represented by the selected key performance indicators, i.e., H2 purity, H2 yield, CH4 conversion, cold gas efficiency (CGE), net efficiency (NE), fuel consumption for the sorbent regeneration step, and CO2 capture efficiency. H2 with a purity of 98.5 vol % and a CGE of 75.7% with zero carbon emissions can be achieved. When adding a PSA unit, nearly 100% H2 purity and CO2 capture efficiency were achieved with a CGE of 77.3%. The use of oxy-fuel combustion during regeneration lowered the net efficiency of the process by 2.3% points (since it requires an air separation unit) but allowed the process to achieve negative carbon emissions.
Keywords: Biogas; CH4/CO2 composition; Hydrogen; Sorption enhanced steam reforming; Process simulation; CO2 capture